HPV-Related Cancer Prevention and Control Programs at Community-Based HIV/AIDS Service Organizations: Implications for Future Engagement - Wigfall, Lisa T.; Bynum, Shalanda A.; Brandt, Heather M.; Sebastian, Neethu; Ory, Marcia G. (Frontiers in Oncology, 2018)
Background: People living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and, men who have sex with men (MSM) are disproportionately affected by genital warts and cancers caused by human papillomavirus (HPV). We assessed community-based HIV/AIDS service organizations’ (ASOs) staff awareness, knowledge, attitudes, and beliefs about HPV and effective cancer prevention tools, namely HPV vaccination, Pap and HPV tests. The potential engagement of ASO staff in future efforts to reduce the disproportionate burden of genital warts and HPV-associated cancers among HIV-positive women and MSM was explored. Methods: In May-June 2016, staff were recruited from three ASOs located in the South United States Census region – a geographical area disproportionately affected by HIV/AIDS. Participants completed a 30-minute self-administered, 118-item paper and pencil survey about HPV and cancer. Data analysis was conducted using Stata/SE 14.2. Results: ASO staff (n=30) were 83% non-Hispanic Black, 40% lesbian/gay, and worked with people living with HIV for an average of 11.4±7.7 years. All reported hearing of HPV and 77% had heard of the HPV vaccine (n=23). While all knew HPV can cause cervical cancer, only 67% knew HPV can cause anal cancer. Most (61%) thought the HPV vaccine could prevent cervical cancer. Fewer (39-48%) thought the HPV vaccine could prevent anal, oral, penile, vaginal, and vulvar cancers. All were willing to encourage MSM and female clients to talk to a healthcare provider about HPV vaccination. Almost all were willing to promote HPV vaccination to clients (91-95%) and navigate clients to adult safety net HPV vaccine providers (86-95%). More than half (59-67%) thought they could positively influence their MSM and female clients’ HPV vaccine decision-making. Conclusion: HPV vaccination and the Pap and HPV tests are effective cancer prevention tools that can reduce the disproportionate burden of genital warts and HPV-associated cancers among HIV-positive women and MSM. Engaging ASO staff in cancer prevention efforts may increase HPV vaccination rates and early detection of HPV-associated cancers among HIV-positive women and MSM. Exploring ASOs as community-based settings for promoting effective cancer prevention tools may foster opportunities to reduce the disproportionate burden of genital warts and HPV-associated cancers among HIV-positive women andMSM.